Antiperistaltic lleoproctostomy after total colectomy for chronic ulcerative colitis - Badano Repetto, José Luis (Cirugía del Uruguay, 1975)
A technique is explained whereby transit through natural channels is re-established after total colectomy preserving the rectum, as practiced in a young female patient suffering from severe chronic ulcerative colitis. ·The functional results were excellent and continue six years after operation was performed. The characteristics of this technique consist in employing a simple artifice, by which the Jast segment of the ileon remains in antiperistaltic position, that is, effecting an antiperistaltic ileoprocto